Assessment of Left Atrial Function by Echocardiography: Novel Insights - Hoit, Brian D. (Current cardiology reports, 2018)
Purpose of Review To review the current status of measuring left atrial functions with echocardiography and the ability of atrial functional analysis to predict cardiovascular outcomes. Recent Findings An increasing body of data suggests that left atrium (LA) function assessed with echocardiography provides incremental prognostic information in general and referral populations, and in patients with atrial fibrillation, stroke, heart failure, and ischemic and valvular heart disease. In addition to volumetric analysis and spectral and tissue Doppler, deformational (strain and strain rate) imaging has most recently been used to assess LA reservoir, conduit, and booster pump functions and predict cardiovascular events. Summary Studies of LA function provide new insights into the contribution of LA performance to cardiovascular disease and are promising tools for predicting cardiovascular events in healthy subjects and patients with heart disease. However, robust clinical outcome data from large prospective outcome trials are needed to confirm the incremental predictive ability of these LA functional measures before they are widely accepted.